In Silico Studies on Anti-Stress Compounds of Ethanolic Root Extract of Hemidesmus indicus L. - Daddam, Jayasimha R.; Sreenivasulu, Basha; Umamahesh, Katike; Peddanna, Kotha; Rao, Dowlathabad M. (Current Pharmaceutical Biotechnology, 2020)
Background: Alternative medicine is available for those diseases which cannot be treated by conventional medicine. Ayurveda and herbal medicines are important alternative methods in which the treatment is done with extracts of different medicinal plants. This work is concerned with the evaluation of anti-stress bioactive compounds from the ethanolic root extract of Hemidesmus indicus. Methods: Gas chromatography and Mass Spectrum studies are used to identify the compounds present in the ethanolic extract based on the retention time, area. In order to perform docking studies, Vasopressin model is generated using modeling by Modeller 9v7. Vasopressin structure is developed based on the crystal structure of neurophysin-oxytocin from Bos taurus (PDB ID: 1NPO_A) collected from the PDB data bank. Using molecular dynamics simulation methods, the final predicted structure is obtained and further analyzed by verifying 3D and PROCHECK programs, confirmed that the final model is reliable. The identified compounds are docked to vasopressin for the prediction of anti-stress activity using GOLD 3.0.1 software. Results: The predicted model of Vasopressin structure is stabilized and confirmed that it is a reliable structure for docking studies. The results indicated ARG4, THR7, ASP9, ASP26, ALA32, ALA 80 in Vasopressin are important determinant residues in binding as they have strong hydrogen bonding with phytocompounds. Among the 21 phytocompounds identified and docked, molecule Deoxiinositol, pentakis- O-(trimethylsilyl) showed the best docking results with Vasopressin. Conclusion: The identified compounds were used for anti-stress activity by insilico method with Vasopressin which plays an important role in causing stress and hence selected for inhibitory studies with phytocompounds. The phytocompounds are inhibiting vasopressin through hydrogen bodings and are important in protein-ligand interactions. Docking results showed that out of twenty-one compounds, Deoxiinositol, pentakis-O-(trimethylsilyl) showed best docking energy to the Vasopressin.
Keywords: GC-MS